Examining the relationship between performance-based and questionnaire assessments of executive function in young preterm children: Implications for clinical practice. Issue 7 (3rd October 2019) - O'Meagher, Sari; Norris, Kimberley; Kemp, Nenagh; Anderson, Peter
ABSTRACT: The aim of this study was to determine whether specific performance-based executive function assessment tools were associated with executive functioning in everyday life as reported by parents and teachers of four- to five-year-old preterm and term children. At the age of 4 years, 141 preterm children born <33 weeks' gestation and 77 term children were assessed using performance-based intelligence (WPPSI-III) and executive function (EF) assessment tools (NEPSY-II, Day-Night and Shape School tasks). The assessment results were compared with the parent and teacher completed questionnaires of EF (BRIEF-P) when the children started kindergarten at the age of 4 to 5 years. The performance-based intelligence and EF assessment results were not consistently associated with the parent and teacher reports of EF in everyday life for either preterm or term groups. Clinical implications of using and interpreting performance-based EF assessment tools and EF questionnaires are discussed with a particular focus on young preterm children at the commencement of formal schooling.